ANALISIS SIKAP DAN MINAT MASYARAKAT DALAM MENGEMBANGKAN INDUSTRI KREATIF BATIK DI DESA GAMBARSARI KECAMATAN KEMANGKON KABUPATEN PURBALINGGA - Jati, Eling Purwanto; Indriati, Suci; Astogini, Dwiwiyati; Zulaikha, Siti (Performance, 2013)
Batik’s Creative Industries is one of craft sub-sector that potential to be developed . Batik Purbalingga is one of the creative industries that actually can be developed well, but face some problems such as : only have a few motives, using simple equipment, narrow market access because it only relies on collectors, lack of business management, lack of administration and accounting records because it was mixed with the family finances. Regeneration batik artisans become a major problem, as well. One of the Government's efforts to tackle the problems is by creating new batik entrepreneur through training in order to develop batik creative industries in Purbalingga. This research was conducted with the aim to analyzed the attitudes and interests of Gambarsari villagers in developing creative industries Batik Purbalingga, based on Theory of Planned Behaviour (TPB) approach, by analyzing the influence of Attitude, Subjective Norms and Behavioral Control against the public interest in develop batik industry creative in Gambarsari. By using multiple regression analysis applied on a sample of 100 respondents in the study, the results obtained showed that Attitude, Subjective norm, and Perceived Behavioral Control has a positive significant effect on Behavioral Intention or interest of Gambarsari villagers to develop batik creative industries, either simultaneously and partially. By using the elasticity test, can be concluded that Perceived Behavioral Control is variable that most affect the Behavioral Intention or interest of Gambarsari villagers to develop Purbalingga’s batik creative industries.